Tahsin Learning in Reading the Qur'an for Children at the Hidayatul Mubtadien Prayer Room, Jengkok Village, Kertasemaya District, Indramayu Regency - Siti Fatihatul Hasanah (Aslama: Journal of Islamic Studies, 2024)
This tahsin learning activity aims to enable the children of Jengkok Village to improve, enhance, embellish, and beautify their reading in reading the Qur'an. So that when reading the Qur'an, the person who hears it does not misunderstand the contents of the verses of the Qur'an being read. The method used in this program is the discussion method and also direct practice, such as the teacher first reading the verses of the Qur'an then followed by the students. This supporting program also uses an approach. The approach in this program uses a phenomenological approach, the phenomenological approach can be started by observing and examining the target objects of the program implemented in Jengkok Village. The program carried out is tahsin learning in the program to improve the reading of the Qur'an which is expected to be able to increase the interest and enthusiasm of children in learning tahsin. This activity is carried out in three stages, namely: pretest, provision of materials and posttest. The targets of this study are children of various age levels, school levels and children who have not/are not in school who live around the location. Many children are enthusiastic about this tahsin learning. Because with this tahsin learning, children can better understand the makhorijul huruf and the science of tajwid in the Qur'an. The implementation of this tahsin learning will be held every day for a period of two weeks. Then in evaluating the results of this tahsin learning, we use pretest and posttest sheets to determine the differences in conditions before and after tahsin learning in these children.